1990
DOI: 10.1002/jat.2550100109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of deoxyguanosine–benzoquinone adducts

Abstract: Benzene expresses its carcinogenic potential in humans largely in the form of acute leukemia. Because an understanding of the formation of DNA adducts by benzene metabolites may help to explain the etiological role they play in benzene-induced bone marrow disease, we have synthesized, isolated and characterized adducts formed by the reaction of deoxyguanosine with hydroquinone and p-benzoquinone, two toxic metabolites of benzene. [3H]Deoxyguanosine and [14C]hydroquinone reacted in neutral aqueous buffer contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 17 publications
(1 reference statement)
2
55
0
Order By: Relevance
“…To chemically characterize the DNA adducts formed, adducts were prepared in vitro by reacting deoxynucleosides or deoxynucleoside monophosphates with either p-benzoquinone or hydroquinone in the presence of an oxidizing agent. The combination of UV, fluorescence, mass, and nuclear magnetic resonance spectrometry was first used by Jowa et al (29) to identify 3'-OH-1,N2-benzetheno-2'-deoxyguanosine as a major deoxyguanosine adduct ( Figure 5). …”
Section: Microsomal Metabolismmentioning
confidence: 99%
“…To chemically characterize the DNA adducts formed, adducts were prepared in vitro by reacting deoxynucleosides or deoxynucleoside monophosphates with either p-benzoquinone or hydroquinone in the presence of an oxidizing agent. The combination of UV, fluorescence, mass, and nuclear magnetic resonance spectrometry was first used by Jowa et al (29) to identify 3'-OH-1,N2-benzetheno-2'-deoxyguanosine as a major deoxyguanosine adduct ( Figure 5). …”
Section: Microsomal Metabolismmentioning
confidence: 99%
“…Identification of (3'OH)benzetheno-(N1,N2)-deoxyguanosine as a DNA adduct by Jowa et al (3,14) was confirmed by Snyder et al (4) and Kaur et al. (5).…”
Section: Introductionmentioning
confidence: 88%
“…[10][11][12] Both metabolites form exocyclic benzetheno adducts with dG, dA and dC. [13][14][15][16][17] Although they were not detected 4 in tissues such as the bone marrow by 32 P-postlabeling, [18,19] their in vivo formation by similar mechanisms to those seen in in vitro reactions is expected, given that the yields of these adducts were high in the latter. Using site-directed mutagenesis, we recently showed that all three p-BQ adducts are highly mutagenic in S. cerevisiae by predominantly causing deletion mutations.…”
Section: Introductionmentioning
confidence: 99%